2010
DOI: 10.1021/ja1065448
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing and Tuning Thermodynamic Dispersion in Metalloprotein Monolayers

Abstract: In coupling the redox state of an adsorbed molecule to its spectral characteristics redox profiles can be directly imaged by means of far-field fluorescence. At suitable levels of dilution, on optically transparent electrode surfaces, reversible interfacial electron transfer processes can be followed pixel by pixel down to scales which approach the molecular. In mapping out switching potentials across a surface population, thermodynamic dispersion, related to variance in the orientation, electronic coupling, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 98 publications
3
23
0
Order By: Relevance
“…26,36,37 The width of the distribution (45 mV) is narrower than those previously reported in singlemolecule studies of Az. Davis et al 38 reported a FWHM of 150 mV in a study where each E 0 was calculated from a cluster of about 1000 molecules. Salverda et al 13 reported a width of 70 mV where each value was obtained from hundreds of isolated Az molecules on the surface.…”
Section: Single-molecule Midpoint Potentialsmentioning
confidence: 99%
“…26,36,37 The width of the distribution (45 mV) is narrower than those previously reported in singlemolecule studies of Az. Davis et al 38 reported a FWHM of 150 mV in a study where each E 0 was calculated from a cluster of about 1000 molecules. Salverda et al 13 reported a width of 70 mV where each value was obtained from hundreds of isolated Az molecules on the surface.…”
Section: Single-molecule Midpoint Potentialsmentioning
confidence: 99%
“…To obtain a 10 mV gain in W 1/2 by including only the E 0 dispersion, we would have to use roughly four times this experimentally measured spread in E 0 values, and a 20 mV W 1/2 21 to be applicable to metalloprotein monolayers. It is of course possible that the distribution of E 0 values in modified azurin metalloprotein films is smaller than in other types of films due to the generally buried (environmentally screened) nature of the redox sites, but a direct measurement of distributions on other systems is needed to confirm whether this hypothesis is correct.…”
Section: ■ Theorymentioning
confidence: 99%
“…[1][2][3][4]6,[20][21][22]25 It is important to note that the field of surface-confined electrochemistry is considerably more complex and hence less well understood than its solution-phase counterpart. Importantly, parameter estimations are dependent on potentially problematic modeling assumptions.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…[116,117] The stabilityo fa zurin on such alkanethiol SAMs has been put to particularly good use in the quantification of kinetic and thermodynamic dispersion, through the coupling of fluorescence monitoring of the copperr edox state with electrochemical control of the redox potential. [118,119] The immobilization of proteins which interact well with negativelyc harged PGE electrodes has been achieved throught he use of carboxylic-acid-terminated SAMs. [105][106][107][108][109]120] This has been probedi nd etail using cytochrome c, ap rotein thought to transfer electrons throughi nteraction with redox partners that are attracted to the positively chargeds urface lysine moieties close to the redox-activeh aem group.…”
Section: Single-component Sams On Goldmentioning
confidence: 99%